Effect of smear layer on calcium hydroxide removal from root canal using different systems: An ex-vivo study - Anantkumar A Heda; Narendrakumar U Manwar; Akshita G Rathi; Gayatri Deshmukh; Neelam Rahul; Deepashri A Tekam; Chandani M Bhatia (Wolters Kluwer Medknow Publications, 2022)
Background: For successful multi-visit endodontic treatment, clinicians often use calcium hydroxide as an intracanal medicament, and it is necessary to completely remove it from canal before obturation. Presence or absence of a smear layer may play an important role in the removal of calcium hydroxide from root canal systems. Objectives: This study aimed to evaluate the effect of the smear layer on the removal of calcium hydroxide from root canal walls using manual files, ultrasonic files, and an EndoActivator System under a stereomicroscope and to evaluate the effect of sodium hypochlorite solution and ethylenediaminetetraacetic acid (EDTA) solution with sodium hypochlorite solution on the removal of the smear layer from root canals during biomechanical preparation. Methods: A total of 80 extracted premolars were decoronated. They were divided into groups and subgroups, and then further evaluation was performed. Root canal instrumentation was done using #25, 0.06 taper nickel-titanium rotary files (Neoendo, Orikam, Gurgaon, India) using the crown-down technique. Samples were divided into two groups: Group A (with a smear layer) and Group B (without a smear layer), for the placement of calcium hydroxide. They were then divided into three subgroups to evaluate the removal of calcium hydroxide from root canal walls using manual files, ultrasonic files, and an EndoActivator and were examined under a stereomicroscope at magnification 10× with image analysis software. Statistical analysis was performed using analysis of variance and Tukey's post-hoc test. Results: The removal of calcium hydroxide from dentinal walls was significantly better in Group B (p <0.05) than in Group A in cervical, middle, and apical third of the canals. Conclusion: Removal of calcium hydroxide was more efficient in Group B (smear-free) than in Group A (with a smear layer), regardless of the technique used. A comparison of the techniques showed that ultrasonic files were more efficient in removing calcium hydroxide than manual files and EndoActivator System in both study groups.